SPP1 genotype and glucocorticoid treatment modify osteopontin expression in Duchenne muscular dystrophy cells. (8th June 2017) - Vianello, Sara; Pantic, Boris; Fusto, Aurora; Bello, Luca; Galletta, Eva; Borgia, Doriana; Gavassini, Bruno F.; Semplicini, Claudio; Sorarù, Gianni; Vitiello, Libero; Pegoraro, Elena
Abstract: Glucocorticoids are beneficial in Duchenne muscular dystrophy (DMD). Osteopontin (OPN), the protein product of SPP1, plays a role in DMD pathology modulating muscle inflammation and regeneration. A polymorphism in the SPP1 promoter (rs28357094) has been recognized as a genetic modifier of DMD, and there is evidence suggesting that it modifies response to glucocorticoid treatment. The effect of the glucocorticoid deflazacort on SPP1 mRNA and protein expression was investigated in DMD primary human myoblasts and differentiated myotubes with defined rs28357094 genotype (TT versus TG). Both healthy and DMD myoblasts/myotubes abundantly express OPN. In immunoblot, OPN was detected as a doublet of 55 and 50 kDa bands, with a shift towards the lighter isoform in the transition from myoblasts to myotubes and to mature muscle. A significant increase in OPN expression was observed in DMD myotubes carrying the TG compared to the TT genotype at rs28357094. Deflazacort treatment led to a significant increase of OPN only in myotubes carrying the TG genotype, leading to OPN overexpression. Our study shows a strong effect of the rs28357094 G allele in increasing OPN expression in the presence of deflazacort, and adds to the evidence that rs28357094 polymorphism may predict response to glucocorticoids in DMD.